Structured audio, Kolmogorov complexity, and generalized audio coding. - Scheirer, E.D.
Structured-audio techniques are a development in audio coding that develop new connections between the existing practices of audio synthesis and audio compression. A theoretical basis for this coding model is presented, grounded in information theory and Kolmogorov complexity theory. It is demonstrated that algorithmic structured audio can provide higher compression ratios than other techniques for many audio signals and proved rigorously that it can provide compression at least as good as every other technique (up to a constant term) for every audio signal. The MPEG-4 structured audio standard is the first practical application of algorithmic coding theory. It points the direction toward a new paradigm of generalized audio coding, in which structured-audio coding subsumes all other audio-coding techniques. Generalized audio coding offers new marketplace models that enable advances in compression technology to be rapidly leveraged toward the solution of problems in audio coding
Keywords: Kolmogorov complexity; MPEG-4 structured audio standard; Algorithmic coding theory; Algorithmic structured audio; Audio compression; Audio synthesis; Compression ratios; Generalized audio coding; Information theory; Structured-audio techniques